EXPLORING THE CATEGORIZATION OF SOCIO-LINGUISTIC CONCEPTS - Jumaniyozova Shakhlo Zohid kizi (PEDAGOGS, 2024)
The categorization of socio-linguistic concepts plays a pivotal role in understanding the intricate interplay between language and society. From dialects and accents to social identities and power dynamics, socio-linguistic concepts encompass a diverse range of phenomena that shape communication patterns and cultural practices. This article delves into the categorization of socio-linguistic concepts and examines how they contribute to the construction of social meaning and identity.